Missões, religião e educação: a Escola Normal Regional Nossa Senhora da Assunção - Guimarães/MA (1957-1967) - Santiago, Alda Margarete Silva Farias (2019)
The social transformations that took place during the 20th century indicated continuities, reconfigurations, and ruptures in all sectors of Brazilian society. In this perspective, we highlight the relations between the Brazilian State and the Catholic Church, as well as its unfolding in the scope of formal education, starting points for this research, which deals with the memories of the Canadian Missions in the municipality of Guimarães/MA and, in a special way, discusses the foundation and operation of the Escola Normal Regional Nossa Senhora da Assunção in the context of a set of educational actions, in the period from 1957 to 1967. It is also considered the events resulting from the redefinitions of the Church's role in the world, specifically in Brazil, which favored the coming of the Canadian Missions to the north of Maranhão, where the municipality of Guimarães is located. The Congregation of the Sisters of the Assumption of the Blessed Virgin, from the Parish of Saint Gregoire - Diocese of Nicolet/Canadá, stands out as the creator of the educational action that resulted in the creation of that school. We emphasize the need for studies on the History of Education in Brazil, School Institutions, Teacher Training, School Material Culture and its subjects. Thus, this qualitative research is based on the theoretical contributions of Cultural History, through the studies of Freire (1999), Chartier (1990), Certeau (2005; 2012), Elias (1994; 2001) and Benjamin (2013), among others. The Oral History approach is also used, with the contributions of Pesavento (2002), Halbawchs (2006), Alberti (2013) and Jucá (2003), in order to identify, through the subjects' narratives and the analysis of official documents, newspapers and correspondence, the importance of the Escola Normal and its repercussions, as well as the other initiatives undertaken by the other Congregations that integrated the Missions, through the representations present in the oral and documentary sources. Therefore, a brief history of the municipality of Guimarães and its characteristics is prioritized, which allows a better understanding of the work of the religious. The results indicate the vitality of the educational work and also point out pertinent aspects about teacher training, the expansion of schooling and the insertion of subjects in formal productive activities, through the teaching profession; in addition to several other information about the period investigated, which attest to the relevance of the research.